VD_FINDINFO ML / 2012 / 72 vom 11. April 2012 - VD Tribunal cantonal (2012)
REQUÊTE DE MAINLEVÉE, MEILLEURE FORTUNE, NOTIFICATION IRRÉGULIÈRE, NULLITÉ | 265a al. 1 LP, 82 LP, 138 al. 3 let. a CPC (CH)